The characterisation of Vitis vinifera ’Refošk’ with AFLP and SSR molecular markers and ampelographic traits - Matjaž HLADNIK; Jernej JAKŠE; Dunja BANDELJ; Irma VUK (Acta Agriculturae Slovenica)
The genetic diversity and ampelographic variability of autochthonous red wine cultivar ‘Refošk’ (Vitis vinifera L.) grown in Slovenia were evaluated with AFLP molecular markers and OIV descriptors, respectively. SSR molecular markers were employed to confirm cultivar identity of analysed samples. Eight AFLP primer combinations, one was monomorphic, produced 16 polymorphic markers in 41 out of 113 samples, what classified samples into monomorphic and polymorphic group. Dendrogram constructed with simple matching coefficient and unweighted pair-group method analysis presented genetic diversity within polymorphic group. Refošk biotypes from monomorphic and polymorphic groups were evaluated with 22 OIV descriptors related to bunch, berry and must, but on the basis of ampelographic characterization samples were not differentiated among two major groups obtained with AFLP analysis. Results of genetic analysis indicated that ‘Refošk’ originated from closely related plants that are phenotypically very similar. With regard to low observed genetic diversity more attention should be dedicated to the selection in order to conserve remaining genetic diversity.